Front Matter - Romi Cendra (UIR Press, 2019)
Journal Sport Area publishes research journals and critical analysis studies in the areas of Sport Education, Sports Coaching and Sports Science. The theme of the paper covers: Learning Physical Education and Sport, Sport Pedagogy, Sports Sociology, Sport Psychology, Sports Coaching, Sports Science, Sports Management, Sports Biomechanics, Health Sports, Sports Philosophy, Sports Industry, and Sports Physiology. Journal Sport Area publish 2 times annually (June and December).